AI IN FATWA FORMULATION: TRANSFORMING SHARIA-COMPLIANT FINANCE - Priantina, Anita; Mimma Maripatul Uula; Aufa; Evania Herindar (Bank Indonesia, 2025)
Fatwas play a pivotal role in Islamic jurisprudence, serving as legal instruments to ensure that financial practices align with Shariah principles. For Islamic financial institutions, timely and accurate fatwas are essential to maintain compliance, operational clarity, and stakeholder trust. However, the fatwa development process is often time intensive. This study examines how artificial intelligence (AI) can be leveraged to enhance the efficiency and responsiveness of fatwa formulation. Using the Analytic Network Process (ANP), Shariah advisors and members of the Shariah Supervisory Board of Islamic Financial Institutions assessed the benefits, costs, opportunities, and risks associated with AI adoption. AI’s capacity for comprehensive data analysis is found to be the most weighted benefit. Key concerns include the cost of scientific verification, the risk of automating sacred decision-making, and the weakening of istinbath (legal reasoning) by scholars. To harness AI’s potential while preserving the integrity of Islamic jurisprudence, it is essential to have appropriate tools, training, and governance frameworks in place. AI has the potential not only to streamline the issuance of fatwas but also to transform the responsiveness and scalability of Shariah-compliant financial services. This study contributes to the literature on AI and Islamic jurisprudence by presenting an evidence-based framework for the responsible integration of AI in Shariah governance.